2020
DOI: 10.14311/ap.2020.60.0369
|View full text |Cite
|
Sign up to set email alerts
|

DEVELOPMENT OF NUMERICAL MODELS FOR THE PREDICTION OF TEMPERATURE AND SURFACE ROUGHNESS DURING THE MACHINING OPERATION OF TITANIUM ALLOY (Ti6Al14V)

Abstract: Temperature and surface roughness are important factors, which determine the degree of machinability and the performance of both the cutting tool and the work piece material. In this study, numerical models obtained from the Response Surface Methodology (RSM) and Artificial Neural Network (ANN) techniques were used for predicting the magnitude of the temperature and surface roughness during the machining operation of titanium alloy (Ti6Al4V). The design of the numerical experiment was carried out using the Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…(2019c) CNC Milling Empirical Tlhabadira et al. (2019) CNC Milling Empirical Daniyan et al. (2020a) CNC Milling Empirical …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2019c) CNC Milling Empirical Tlhabadira et al. (2019) CNC Milling Empirical Daniyan et al. (2020a) CNC Milling Empirical …”
Section: Resultsmentioning
confidence: 99%
“…However, the process sustainability reduces when the temperature exceeds the optimum. One way to keep the temperature within the optimum range is through temperature monitoring in real time via the use of infrared video thermometer or other suitable temperature measuring and monitoring devices ( Daniyan et al., 2020a ). In addition, the use of cutting fluids at the shear zone will reduce the coefficient of friction among the chips, tools and work piece interface ( Okafor and Aramalla, 2006 .…”
Section: Review Of Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The ANOVA evaluates the statistical significance of the output of the model. A good model which validates the numerical experimentation is signalled by a "p-value Prob > F" which should be less than 0.050, a F-value greater than unity, a "Lack of Fit" which is statistically insignificant relative to the pure error, the predicted R square, R squared and the adjusted R Squared which should be within the same range and close to 1 as well as the adequate precision which measures the signal to noise ratio which should be greater than 4 [16].…”
Section: Analysis Of Variancementioning
confidence: 99%
“…Previous studies have shown that preliminary process design with use of the Design of Experiment (DoE) technique via the use of Taguchi, Response Surface Methodology etc. can be employed for the determination of the feasible combinations of process parameters that will enhance excellent mechanical properties [13][14][15][16]. Previous studies have also shown that the microstructure and mechanical properties of brass can also be enhanced with a carefully balanced composition of Cu-Zn and other alloying elements, addition of additives as well as the use of appropriate heat treatment technique [17][18].…”
Section: Introductionmentioning
confidence: 99%